Study of the Effect of Ultraviolet Exposure Duration on Polypropylene Properties - Saputra, Andri; Sitinjak, Tria Madeline; Warmiati; Hermiyati, Indri; Ratnaningsih, Wahyu; Hariyadi, Asful; Nurry, Dennis Farina (Jurnal Sains Materi Indonesia, 2025)
Prolonged exposure to ultraviolet (UV) radiation significantly alters the chemical, thermal, and mechanical properties of polypropylene (PP), leading to degradation and reduced material performance. This study aims to investigate the effect of exposure length to UV on the chemical properties (functional and thermal) and mechanical properties (tensile strength) of PP. Specimens were subjected to UV exposure for 0 (control), 125, 175, 225, 275, 325, 375, and 625 days. FTIR analysis indicates UV exposure chemically degrades polypropylene (PP) by generating new oxygenated groups (–OH and C=O at 3368 cm⁻¹ and 1586 cm⁻¹) and damaging its main molecular structure (C-H at 2949 cm⁻¹, 2867 cm⁻¹, and 841 cm⁻¹). Prolonged UV exposure alters the thermal properties of polypropylene (PP), as indicated by DSC analysis, which shows broadening and shifting of the melting peak (175–180 °C) due to crystallinity changes and increased oxidation. The mechanical properties also deteriorate, with a critical reduction in tensile strength, particularly between 225 and 375 days, indicating an accelerated degradation phase. After 625 days, tensile strength declines by approximately 59%, confirming the substantial impact of extended UV exposure on PP’s durability.